Biochemical changes in serum and urine in bovine fluorosis - Singh, J L; Swarup, D (The Indian Journal of Animal Sciences, 2012)
Biochemical changes in serum and urine were investigated in cow and buffaloes showing clinical signs of fluorosis due to excessive intake of fluoride. As compared to healthy cows and buffaloes significantly higher levels of fluoride were recorded in serum and urine of affected cows and buffaloes which confirmed the diagnosis of fluorosis. The affected animals revealed significantly elevated values of serum urea nitrogen, creatinine inorganic phosphorus, alkaline phosphatase and manganese. The concentration of calcium, magnesium, iron and copper was found declined in fluorotic cows and buffaloes. Changes in urine included significantly increased levels of calcium, phosphorus and alkaline phosphatase in cows and buffaloes suffering from fluorosis. Serum zinc concentration showed no change due to fluoride intoxication in cows.